Analysis of the Strategy of Law Office & Associates “Solidaritas” Pemalang in Providing Restorative Justice for the Surrounding Community - Rusmiyanti, Rusmiyanti; Santoso, Aris Prio Agus (Eastasouth Institute, 2025)
The main problem in this research is that the conventional legal system, which is primarily punitive, often fails to provide fair and holistic redress for both victims and offenders, thereby creating a gap between formal justice mechanisms and the social justice needs of local communities such as those in Pemalang. The purpose of this study is to analyze the strategies employed by Law Office & Associates “Solidaritas” Pemalang in implementing restorative justice as an alternative legal model that emphasizes reconciliation, community participation, and the restoration of social harmony. This study uses a descriptive-analytical method with qualitative analysis, combining literature review, participatory observation, interviews, and documentation to systematically examine the strategies, challenges, and impacts of restorative justice implementation by Law Office & Associates “Solidaritas” Pemalang. The research findings show that the restorative justice strategy of Law Office & Associates “Solidaritas” Pemalang reflects a progressive and participatory legal approach inspired by Marshall, Zehr, and Daly, emphasizing the restoration of social relations and empowerment of marginalized groups. Through mediation, consultation, and empathy-based assistance, the office addresses community needs effectively, fostering trust, awareness, and peaceful dispute resolution. Its success highlights law as social service rather than punishment. To enhance this role, recommendations include capacity building, systematic documentation, stronger collaborative networks, community legal education, and advocacy for supportive regulations, ensuring restorative justice becomes a sustainable and legitimate model.